-.4=(g/3)-.9

Simple and best practice solution for -.4=(g/3)-.9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -.4=(g/3)-.9 equation:



-.4=(g/3)-.9
We move all terms to the left:
-.4-((g/3)-.9)=0
We add all the numbers together, and all the variables
-((+g/3)-.9)-.4=0
We add all the numbers together, and all the variables
-((+g/3)-.9)-0.4=0
We multiply all the terms by the denominator
-((+g-(0.4)*3)-.9)=0
We calculate terms in parentheses: -((+g-(0.4)*3)-.9), so:
(+g-(0.4)*3)-.9
We add all the numbers together, and all the variables
(+g-(0.4)*3)-0.9
We calculate terms in parentheses: +(+g-(0.4)*3), so:
+g-(0.4)*3
determiningTheFunctionDomain g-(0.4)*3
We add all the numbers together, and all the variables
g-1.2
Back to the equation:
+(g-1.2)
We get rid of parentheses
g-1.2-0.9
We add all the numbers together, and all the variables
g-2.1
Back to the equation:
-(g-2.1)
We get rid of parentheses
-g+2.1=0
We add all the numbers together, and all the variables
-1g+2.1=0
We move all terms containing g to the left, all other terms to the right
-g=-2.1
g=-2.1/-1
g=2+0.1/1

See similar equations:

| a*3=-30 | | 6b^-13b+6=0 | | (5x+7)/x-1=3x+2 | | -32=-3+7×+3(x-2) | | 11/4x=9 | | 3x+9=#x-9 | | 2y-2(8+2y)-4=-2 | | 4m+5/3=2m-3 | | 14(x+)-10x=8 | | y-4/2=-5 | | 2.5t=7 | | 7n-3n+15=0 | | 14(x+3)-111111111110x=8 | | 6b^-13b=-6 | | x/2=17x/4+6/7 | | 3/4(8t-4)=18 | | 8c+10=42 | | n-5/5=10 | | 8t-28=-23+26t | | 11p=-77 | | |x|+2=5 | | 175m-100m+42975=45900-150m | | 3*2^x-16=80 | | 6m+22+6m-5=0 | | 4(r+1)=-5r+31 | | 3/5n+9/10=-1/5n-3/14 | | p/2+10=9 | | 8-28=-23+26t | | -180/y=`5 | | 1x1/3+1=8 | | 18+18+15+15+15+x=93 | | x/4+3=2(x-2) |

Equations solver categories